Modelling production ramp-up of engineering products - Ball, Peter D.; Roberts, S.; Natalicchio, A.; Scorzafave, C. (Professional Engineering Publishing, 2011)
Companies that introduce new products quickly have been shown to be better performers. The effectiveness of the new product introduction process is critical to their performance. Production ramp-up is a necessary phase of new product introduction, and both planning and execution need careful consideration, especially for engineered products, which are generally typified by design, purchasing, and production complexity. Better understanding of the issues, and more effective modelling of options, should lead to more predictable and quicker ramp-up. Examination of the literature, however, reveals that little attention has been paid to this area. What knowledge does exist tends to concentrate on specific aspects such as capacity or learning or costs. This paper reviews the ramp-up literature in general, along with the specific components in more detail, to establish how current work can be combined to develop the architecture for a modelling tool for engineering product ramp-up. The contribution of the paper is to provide a wider view of ramp-up, to present it as a topic worthy of consideration in its own right, and to introduce a prototype modelling tool that can aid the investigation and solutions of the issues that the paper raises.
Keywords: production ramp-up modelling; learning curves, new product introduction, engineering products